Pathogenicity Determinants of the Human Malaria Parasite Plasmodium falciparum Have Ancient Origins - Andrew J. Brazier (American Society for Microbiology, 2017)
ABSTRACT Plasmodium falciparum, the most deadly of the human malaria parasites, is a member of the Laverania subgenus that also infects African Great Apes. The virulence of P. falciparum is related to cytoadhesion of infected erythrocytes in microvasculature, but the origin of dangerous parasite adhesion traits is poorly understood. To investigate the evolutionary history of the P. falciparum cytoadhesion pathogenicity determinant, we studied adhesion domains from the chimpanzee malaria parasite P. reichenowi. We demonstrate that the P. reichenowi var gene repertoire encodes cysteine-rich interdomain region (CIDR) domains which bind human CD36 and endothelial protein C receptor (EPCR) with the same levels of affinity and at binding sites similar to those bound by P. falciparum. Moreover, P. reichenowi domains interfere with the protective function of the activated protein C-EPCR pathway on endothelial cells, a presumptive virulence trait in humans. These findings provide evidence for ancient evolutionary origins of two key cytoadhesion properties of P. falciparum that contribute to human infection and pathogenicity. IMPORTANCE Cytoadhesion of P. falciparum-infected erythrocytes in the microcirculation is a major virulence determinant. P. falciparum is descended from a subgenus of parasites that also infect chimpanzees and gorillas and exhibits strict host species specificity. Despite their high genetic similarity to P. falciparum, it is unknown whether ape parasites encode adhesion properties similar to those of P. falciparum or are as virulent in their natural hosts. Consequently, it has been unclear when virulent adhesion traits arose in P. falciparum and how long they have been present in the parasite population. It is also unknown whether cytoadhesive interactions pose a barrier to cross-species transmission. We show that parasite domains from the chimpanzee malaria parasite P. reichenowi bind human receptors with specificity similar to that of P. falciparum. Our findings suggest that parasite adhesion traits associated with both mild and severe malaria have much earlier origins than previously appreciated and have important implications for virulence evolution in a major human pathogen.